2010
DOI: 10.1017/s0029665110003824
|View full text |Cite
|
Sign up to set email alerts
|

Improving peri-operative fluid management in a large teaching hospital: pragmatic studies on the effects of changing practice

Abstract: Concerns about the over-prescription of peri-operative fluids, particularly normal saline, culminated in the recent publication of UK national guidelines on fluid prescription during and after surgery. A working group comprising members of the nutrition support team, surgeons, anaesthetists and pharmacists therefore sought to reduce the overall levels of fluid prescription and to limit normal saline usage in our large Teaching Hospital by producing written local fluid prescribing guidelines and holding a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The British Consensus Guidelines on Intravenous Fluid Therapy for Adult Surgical Patients (GIFTASUP) recommend appropriate IV fluid prescribing in the pre-operative and postoperative period. Recent prospective surveys, using historical controls, suggested that guidelines and instruction on fluid management could improve outcome [9,18]. Teaching on these important clinical skills should use uniform guidance to avoid inconsistencies, and ideally in clinical surroundings with practical experience, such as “pre-prescribing” [19].…”
Section: Discussionmentioning
confidence: 99%
“…The British Consensus Guidelines on Intravenous Fluid Therapy for Adult Surgical Patients (GIFTASUP) recommend appropriate IV fluid prescribing in the pre-operative and postoperative period. Recent prospective surveys, using historical controls, suggested that guidelines and instruction on fluid management could improve outcome [9,18]. Teaching on these important clinical skills should use uniform guidance to avoid inconsistencies, and ideally in clinical surroundings with practical experience, such as “pre-prescribing” [19].…”
Section: Discussionmentioning
confidence: 99%
“…The balanced crystalloid solutions were the most common postoperative fluid, with hypotonic crystalloids (dextrose-saline solutions) and 0.9 % sodium chloride as the next most common. There is increasing recognition that the traditional postoperative regime of 0.9 % sodium chloride and 5 % dextrose risks sodium, chloride and salt overload (De Silva et al 2010 ). Sodium chloride (0.9 %), even when not given in excessive quantities, is associated with a variety of detrimental effects such as hyperchloraemic acidosis, reduced renal blood flow, increased chance of renal failure and increased in-hospital mortality after major abdominal surgery (Lobo 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sodium chloride (0.9 %), even when not given in excessive quantities, is associated with a variety of detrimental effects such as hyperchloraemic acidosis, reduced renal blood flow, increased chance of renal failure and increased in-hospital mortality after major abdominal surgery (Lobo 2012 ). Data from Wessex in 2007 found that over 70 % of postoperative fluid prescriptions were 0.9 % sodium chloride or 5 % dextrose (De Silva et al 2010 ). This figure was reduced to 40 % in 2009 after a targeted education intervention (De Silva et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations